Depressive disorders among Tunisian high school teachers in the face of COVID-19 - N. Regaieg; L. Zouari; Y. Mejdoub; R. Feki; I. Gassara; N. Smaoui; S. Omri; M. Maalej; J. Ben Thabet; N. Charfi; M. Maalej (European Psychiatry, 2022)
Introduction The constraints linked to COVID-19 may reduce resilience and intensify depressive feelings especially in vulnerable populations such as teachers.